Biological characteristics and genomic analysis of a novel Vibrio parahaemolyticus phage phiTY18 isolated from the coastal water of Xiamen China - Liu, Bo; Zheng, Tingyi; Quan, Rui; Jiang, Xinglong; Tong, Guixiang; Wei, Xinxian; Lin, Mao (Frontiers in Cellular and Infection Microbiology, 2022)
Vibrio parahaemolyticus is a common pathogen usually controlled by antibiotics in mariculture. Notably, traditional antibiotic therapy is becoming less effective because of the emergence of bacterial resistance, hence new strategies need to be found to overcome this challenge. Bacteriophages, a class of viruses that lyse bacteria, can help us control drug-resistant bacteria. In this study, a novel Vibrio parahaemolyticus phage phiTY18 isolated from the coastal water of Xiamen was explored. Transmission electron microscopy showed that phiTY18 had an icosahedral head of 130.0 ± 1.2 nm diameter and a contractile tail of length of 66.7 ± 0.6 nm. The phage titer could reach 7.2×1010 PFU/mL at the optimal MOI (0.01). The phage phiTY18 had a degree of tolerance to heat and acid and base. At the temperature of 50°C (pH7.0, 1h) the survival phages reached 1.28×106 PFU/mL, and at pH 5-9 (30°C, 1h), the survival phages was greater than 6.37×107 PFU/mL Analysis of the phage one-step growth curve revealed that it had a latent period of 10min, a rise period of 10min, and an average burst size of the phage was 48 PFU/cell. Genome sequencing and analysis drew that phage phiTY18 had double-stranded DNA (191,500 bp) with 34.90% G+C content and contained 117 open reading frames (ORFs) and 24 tRNAs. Phylogenetic tree based on major capsid protein (MCP) revealed that phage phiTY18 (MW451250) was highly related to two Vibrio phages phiKT1024 (OM249648) and Va1 (MK387337). The NCBI alignment results showed that the nucleotide sequence identity was 97% and 93%, respectively. In addition, proteomic tree analysis indicated that phage phiTY18, phiKT1024, and Va1 were belong to the same virus sub-cluster within Myoviridae. This study provides a theoretical basis for understanding the genomic characteristics and the interaction between Vibrio parahaemolyticus phages and their host.